Neoadjuvant chemotherapy in patients with breast cancer: Does response in the breast predict axillary node response?. Issue 4 (April 2020) - Morgan, C.; Stringfellow, T.D.; Rolph, R.; Kovacs, T.; Kothari, A.; Pinder, S.E.; Hamed, H.; Sever, A.R.
Abstract: Introduction: Determining the extent of residual disease in the breast and axilla following neoadjuvant chemotherapy (NACT) is vital for surgical planning. Traditionally patients with incomplete radiological response in the breast after NACT undergo axillary node clearance, regardless of axillary clinical and radiological response. The aim of this study was to determine whether radiological and/or pathological response in the breast to NACT were predictive of axillary response. Materials and methods: A retrospective cohort study of patients with operable breast cancer with histologically proven axillary lymph node involvement who received NACT and underwent definitive surgical treatment between 1/1/2016 and 31/12/2018 were included. All had MRI and/or US of the breast and axilla before, mid-treatment and at the end of NACT. Results: The 83 patients had a median age of 50 years (range 25–77). MRI had a positive predictive value (PPV) of 52.6% and negative predictive value (NPV) of 81.8% for breast pathological complete response (pCR). For axillary pCR, US had a PPV of 60.0% and NPV of 89.6%. Only 71% of patients had radiological concordance; 15.9% had radiological complete response (rCR) in breast and axilla whilst 55.1% had neither breast nor axillary rCR. 85.6% of patients had pathological concordance (20.5% with breast and axillary pCR: 65.1% with residual disease in both). Conclusion: Radiological and pathological response in the breast to NACT does not accurately predict axillary response. The axilla and the breast should be viewed and assessed as two separate entities for treatment plans.